2013
DOI: 10.1007/s10103-013-1450-y
|View full text |Cite
|
Sign up to set email alerts
|

Some controversies in endovenous laser ablation of varicose veins addressed by optical–thermal mathematical modeling

Abstract: Minimally invasive treatment of varicose veins by endovenous laser ablation (EVLA) becomes more and more popular. However, despite significant research efforts performed during the last years, there is still a lack of agreement regarding EVLA mechanisms and therapeutic strategies. The aim of this article is to address some of these controversies by utilizing optical-thermal mathematical modeling. Our model combines Mordon's light absorption-based optical-thermal model with the thermal consequences of the thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 15 publications
4
41
1
8
Order By: Relevance
“…This is in the spirit of two other proposed mechanisms that may unlikely dominate the efficacy of EVLA despite suggested importance, i.e., direct laser light absorption by the vein wall [26] and direct contact between fiber tip and vein wall [28]. Concerning the former, comparing zero with normal vein wall absorption in our model simulations gave similar computed wall temperatures, implying a limited importance of direct vein wall light absorption [11]. Concerning the latter, the small vein wall injury line of about 0.6 mm width relative to the vein wall circumference of about 10 to 60 mm (diameters between 3 and 20 mm) was suggested inadequate for vein obliteration [8].…”
Section: The Five Proposed Mechanisms Of Action For Evlasupporting
confidence: 77%
“…This is in the spirit of two other proposed mechanisms that may unlikely dominate the efficacy of EVLA despite suggested importance, i.e., direct laser light absorption by the vein wall [26] and direct contact between fiber tip and vein wall [28]. Concerning the former, comparing zero with normal vein wall absorption in our model simulations gave similar computed wall temperatures, implying a limited importance of direct vein wall light absorption [11]. Concerning the latter, the small vein wall injury line of about 0.6 mm width relative to the vein wall circumference of about 10 to 60 mm (diameters between 3 and 20 mm) was suggested inadequate for vein obliteration [8].…”
Section: The Five Proposed Mechanisms Of Action For Evlasupporting
confidence: 77%
“…Although it would have been preferred to test blood and water at wavelengths where the absorption coefficients of HbO 2 and H 2 O are more alike, the wavelength of 980 nm used in EVLA was applied. We emphasize that the selection of wavelength for EVLA treatment has been subject of much debate; see Poluektova et al [28]. It will be shown that the most striking difference occurring in the experiments with these fluids is related nevertheless to boiling dynamics at the fiber tip as a result of the blood chemical composition.…”
Section: Methodsmentioning
confidence: 87%
“…The carbonized layer absorbs 55% of the energy provided at the fiber tip ( [15]). The extent of the channel volume directly heated by laser light emanating from the fiber tip is primarily determined by radiation absorption in the fluid; see Poluektova et al [28]. Heat conduction from the fiber tip, if it is carbonized and hot, is a second important mechanism of heat transfer to the fluid.…”
Section: Typical Temperature Histories In Water With a Bare Tip 15 Wmentioning
confidence: 99%
See 2 more Smart Citations